Pengembangan Media Crossword Puzzle dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPAS Kelas III D MI NU Metro Lampung - Alvitriani, Alvitriani; Mahmudah, Masrurotul; Aisyah, Nurul (Universitas Nusantara PGRI Kediri, 2025)
This research is a development research (R&D) that aims to develop Crossword Puzzle learning media in the subject of Science on the material about the characteristics of living things in order to improve student learning outcomes. The model used in this study is the 4D model consisting of 4 stages, namely Define, Design, Development and Disseminate. At the develop stage, the researcher validated the media expert and material expert. The subjects of this study were 24 students in class III D in a trial at MI NU Metro Lampung. The results of the study showed the results of media expert validation of 82%, material expert validation of 84% with the criteria